Uji Stabilitas Protein Salep Kombinasi Ikan Gabus (Channa striata) dan Ekstrak Etanol Daun Sirih (Piper betle L.) Menggunakan Metode Kjeldahl - Mohamad Andrie; Wintari Taurina; Maya Widya Astuti Wulandari (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
The endemic snakehead fish (Channa striata) supposed to speed up wound healing. Antibacterial properties of green betel leaf (Piper betle L.) are well known. Wound healing necessitates moist circumstances and prolonged medication contact. Such the fact that ointment fat-based preparation that can moisturize skin or wound area due to extended contact with the skin, increasing absorbance and effectiveness. Fish protein concentrate high-protein concentrate obtained by eliminating fat and water from fish. One way that can used is freeze drying. Using Kjeldahl method, this study intends investigate protein stability of combination freeze dry ointment extract of snakehead fish (Channa striata) and ethanol extract green betel leaf (Piper betle L.). The data was analyzed using the SPSS version 25 app. On day 28, average protein content of freeze dry ointment and a combination of freeze dry ointment in aqueous phase and ethanol extract of green betel leaf was 6.321 % and 6.630 %, respectively, indicating substantial difference in protein content. As result, the freeze dry ointment including aqueous phase and ethanol extract of green betel leaf more stable and has larger protein content than the freeze dry ointment containing snakehead fish extract.